Inhalation aromatherapy for the treatment of comorbid insomnia: a systematic review and meta-analysis - Chen, Hu-Bo; Zhang, Yi-Dan; Qin, Yang; Jiang, Hong-Yu; Wang, Li-Na; Gu, Wei (Frontiers in Psychiatry, 2025)
ObjectiveMeta-analysis can pool multiple studies to explore a particular area in depth, therefore this method was used to explore the clinical efficacy of inhalation aromatherapy for the treatment of comorbid insomnia and provide an empirical evidence for clinical treatment.MethodsThe PubMed, Web of Science, CNKI Database, Wanfang Database, and VIP Database were searched for randomized controlled trials on aromatherapy for the treatment of comorbid insomnia from inception to August 30, 2023. RevMan 5.3 was used for meta-analysis of the results.ResultsA total of 27 publications involving 2072 patients were included. The results of the meta-analysis showed that inhalation aromatherapy well relieved the symptoms of comorbid insomnia (MD -2.90, 95% CI: -3.85 to -1.95, p<0.00001) and the negative mental state of anxiety (MD -3.97, 95% CI: -5.88 to -2.06, p<0.0001) and depression (MD -9.58, 95% CI: -15.13 to -4.03, p=0.0007) in patients. Included studies were heterogeneous, and the factors influencing the heterogeneity were not identified. These studies commonly presented issues such as lack of blinding, and absence of independent testing for the purity or potency of herbs.ConclusionInhalation aromatherapy can improve the sleep quality of patients with other disease states, with basically no adverse reactions and acceptable safety. Therefore, inhalation aromatherapy is expected to become an indispensable complementary therapy in clinical practice for most diseases. However, high-quality clinical trials are still needed to confirm these findings due to methodological weaknesses in blinding and independent testing for the purity and potency of herbs.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023455278.